The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1061/(asce)0733-9445(1995)121:4(634)
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Design of Infilled Frames

Abstract: This paper describes a new method of analysis and design for steel frames with concrete or masonry infilling walls subjected to in-plane forces. The method is based on data generated from previous experiments as well as results from a series of nonlinear finite-element (NLFE) analyses. The method accounts for elastic and plastic behavior of infilled frames considering the limited ductility of infill materials. The proposed method predicts the strength and stiffness of infilled frames as well as the infill diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(145 citation statements)
references
References 14 publications
(12 reference statements)
0
120
0
4
Order By: Relevance
“…The strength predicted by Panagiotakos and Fardis [19] is, on the average, higher than the actual one, while the other models ( [17,18]) underestimate the infill strength. Concerning the stiffness, none of the models reproduce satisfactorily the actual values.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The strength predicted by Panagiotakos and Fardis [19] is, on the average, higher than the actual one, while the other models ( [17,18]) underestimate the infill strength. Concerning the stiffness, none of the models reproduce satisfactorily the actual values.…”
Section: Discussionmentioning
confidence: 91%
“…It is noted that: strength values predicted by Panagiotakos and Fardis [19] are higher than the actual (experimental) ones; the model proposed by Paulay and Priestley [15] and Priestley and Calvi [16] is almost unbiased; the other models tend, on the average, to underestimate the infill strength. The highest and the lowest coefficients of determination are obtained, considering the whole dataset, using the formulation proposed by the Decanini and Fantin [14] and Saneinejad and Hobbs [17], respectively. The comparison between predicted and experimental lateral stiffness is made considering the reduced database.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OOP acceleration can produce infills' collapse by their overturning, which is a great risk for life safety as well as an obstacle to escape/rescue operations during seismic emergency [2]: in this sense, the OOP collapse of infill walls is associable to the attainment of the Life Safety Limit State (LS). A great number of experimental and analytical works concerning the IP behaviour of URM infills is available in literature ( [3][4][5][6], among many others) and some analytical and experimental works have been proposed about their OOP behaviour, especially in recent years ( [7][8][9][10][11][12][13][14][15], among others), and concerning the IP-OOP interaction phenomena, i.e., the effects of IP actions on the OOP behaviour and vice versa. For instance, several authors showed through analytical and experimental studies how the IP displacement demand affects the OOP response of infills in terms of capacity and demand acting on them.…”
Section: Introductionmentioning
confidence: 99%